Tandem deoxygenative hydrosilation of carbon dioxide with a cationic scandium hydridoborate and B(C6F5)3. Issue 1 (29th November 2019) - Beh, Daniel W.; Piers, Warren E.; Gelfand, Benjamin S.; Lin, Jian-Bin
Abstract : A scandium hydridoborate complex supported by the dianionic pentadentate ligand B2 Pz4 Py is prepared via hydride abstraction from the previously reported scandium hydride complex with tris-pentafluorophenyl borane. Abstract : A scandium hydridoborate complex supported by the dianionic pentadentate ligand B2 Pz4 Py is prepared via hydride abstraction from the previously reported scandium hydride complex with tris-pentafluorophenyl borane. Exposure of [(B2 Pz4 Py)Sc][HB(C6 F5 )3 ] to CO2 immediately forms [(B2 Pz4 Py)Sc][HCOOB(C6 F5 )3 ] at room temperature. The formatoborate complex can also be synthesized directly from the starting material (B2 Pz4 Py)ScCl with Et3 SiH and B(C6 F5 )3 while in the presence of an atmosphere of CO2 in 81% yield. This compound was evaluated as the transition metal component of a tandem deoxgenative CO2 hydrosilation catalyst. At 5% loadings, complete consumption of Et3 SiH was observed along with CO2 reduction products, but conversion to an inactive scandium complex identified as (B2 Pz4 Py)ScOSiEt3 was observed.